1969
DOI: 10.1037/h0027032
|View full text |Cite
|
Sign up to set email alerts
|

Social exchange theory: An integrative approach to social conformity.

Abstract: Theoretical and research studies of social conformity are reviewed and integrated through a revised social exchange model. The concept of utility is discarded from the basic economic model in favor of a revealed preference, and this approach is then applied to the existing work on social conformity and approval. The behavior of subjects in conformity and approval studies is assumed to reflect a preference in the manner done in economics. Predictions made from the exchange model are found to be consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(48 citation statements)
references
References 219 publications
(265 reference statements)
1
46
0
Order By: Relevance
“…In his recent review. Nord (1969) has suggested that two things are necessary for PSy'chon. Sei., 1970, Vol.…”
Section: Resultsmentioning
confidence: 99%
“…In his recent review. Nord (1969) has suggested that two things are necessary for PSy'chon. Sei., 1970, Vol.…”
Section: Resultsmentioning
confidence: 99%
“…There has also been limited empirical investigation of the continuity between heterosexist attitudes and behavior (Hornsey et al, 2004). It has been suggested that the contemporary social psychology emphasis on the relationship between attitudes and behavior may have halted the more inclusive study of the effect of social norms on the development of personal attitudes and behavior researched in the 1950s in the conformity studies of Asch (1952,1956) and others (Crutchfield, 1955;Jacobs & Campbell, 1961;Mackie & Smith, 1998;Nord, 1969).…”
Section: Social Conformity and Heterosexismmentioning
confidence: 96%
“…Recently several studies done by experimental social psychologists have demonstrated that individuals faced with an emergency situation are more likely to render aid when alone than when in the presence of others (Darley and Latan6, 1968;Latan6 and Dadey, 1968, 1969, 1970aLatan6 and Rodin, 1969;Schwartz and Clausen, 1970;Levy et al, 1972;Clark and Word, 1972). The typical procedure used by these researchers involves exposing one or more persons to an event which is an emergency but is not without an element of ambiguity, such as the presence of smoke, overhearing an adult or child fall from a chair with accompanying crying and groaning, listening to a seizure victim's plea for help and hearing a maintenance man fall from a ladder.…”
Section: Altruism and Group Sizementioning
confidence: 99%